Association between maternal omega‐3 polyunsaturated fatty acids supplementation and preterm delivery: A proteomic study. Issue 5 (12th March 2020) - Bruschi, Maurizio; Santucci, Laura; Petretto, Andrea; Bartolocci, Martina; Marchisio, Marco; Ghiggeri, Gian Marco; Verrina, Enrico; Ramenghi, Luca A.; Panfoli, Isabella; Candiano, Giovanni
Abstract: Maternal nutrition during pregnancy influences offspring health. Dietary supplementation of pregnant women with (n‐3) long‐chain polyunsaturated fatty acids (PUFA) was shown to exert beneficial effects on offspring, through yet unknown mechanisms. Here, we conducted a dietary intervention study on a cohort of 10 women diagnosed with threatened preterm labor with a nutritional integration with eicosapentaenoic and docosahexaenoic acids. Microvesicles (MV) isolated form arterial cord blood of the treated cohort offspring and also of a randomized selection of 10 untreated preterm and 12 term newborns, were characterized by dynamic light scattering and analyzed by proteomic and statistical analysis. Glutathione synthetase was the protein bearing the highest discrimination ability between cohorts. ELISA assay showed that glutathione synthetase was more abundant in cord blood from untreated preterm compared to the other conditions. Assay of free SH‐groups showed that serum of preterm subjects was oxidized. Data suggest that preterm suffer from oxidative stress, which was lower in the treated cohort. This study confirms that MV are a representative sample of the individual status and the efficacy of dietary intervention with PUFA in human pregnancy in terms of lowered inflammatory status, increased gestational age and weight at birth.